Validity and reliability of the Greek Migraine-Specific Quality of Life Questionnaire (MSQ Version 2.1-GR) - Ermioni Giannouli; Eleni Giannouli; Athanasia Alexoudi; Chryssa Arvaniti; Nikolaos Fakas; Theodoros S. Constantinidis; Evangelos Kouremenos; Dimos-Dimitrios Mitsikostas; on behalf of Hellenic Headache Society (SpringerOpen, 2024)
Abstract Background To assess the validity and reliability of the Migraine-Specific Quality of Life Questionnaire 2.1 (MSQv.2.1) in a group of Greek migraineurs. Design-sample-methods The Greek version of MSQv.2.1 (MSQv.2.1-GR), a self-report measure with 14 items in 3 domains (Role Restrictive (RR), Role Preventive (RP) and Emotional Function (EF)), was administered during a cross-sectional study to 141 Greek adult migraineurs and 135 controls without migraine or any other primary headache disorder, along with Migraine Disability Assessment Scale (MIDAS) and Short Form Health Survey (SF-12) to assess validity. MSQv.2.1-GR was re-administered in a group of participants with migraine two weeks afterwards to assess reliability. Content and construct validity was assessed using Intraclass Correlation Coefficient (ICC), Spearman rho, McDonald's omega, Cronbach's alpha. Confirmatory factor analysis (CFA) was used to test the latent structure of the MSQv.2.1-GR in migraineurs. Results A total of 276 adults participated in the study. Internal consistency of the three MSQv.2.1-GR scales RR, RP and EF yielded a range of McDonald's omega from 0.832 to 0.923 (Cronbach's alpha from 0.814 to 0.923). CFA confirmed the proposed three-factor MSQv.2.1-GR latent structure with acceptable goodness of fit indices and factor loadings. Correlations were established between MSQv2.1-GR component and MIDAS scores, showing moderate and statistically significant relationships (from − 0.519 to −0.562, all p < 0.001) for RR, RP and EF. Correlations between MSQv2.1-GR and SF-12 component scores were identified, with values from 0.1 to 0.4, indicating low to moderate associations. ICC was calculated at 0.997, indicating a high level of reliability between the measures. Notably, all MSQv2.1-GR scores (RR, RP, EF) were significantly higher in the controls compared to migraineurs (p < 0.001 for all scales). These findings suggest that MSQv2.1-GR is internally consistent, shows significant correlations with relevant measures, and is effective in discriminating controls from migraineurs. Conclusion MSQv2.1-GR is a valid and reliable tool to determine the effect migraine has on the quality of life of Greek-speaking migraineurs.